2019
DOI: 10.1167/iovs.19-27565
|View full text |Cite
|
Sign up to set email alerts
|

Blast Preconditioning Protects Retinal Ganglion Cells and Reveals Targets for Prevention of Neurodegeneration Following Blast-Mediated Traumatic Brian Injury

Abstract: Blast preconditioning protects retinal ganglion cells and reveals targets for prevention of neurodegeneration following blast-mediated traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 92 publications
(110 reference statements)
2
26
1
Order By: Relevance
“…Whether these metabolites in the KP affect RGCs was less studied. During our study, a study by Harper et al [25] showed that systemic inhibition of KMO protects RGCs in an experimental mouse model for traumatic brain injury, supporting the idea that KP metabolites play a role in RGC health. We found that the absence of KMO led to higher levels of KYN, KYNA and AA in the serum and retina, coincident with a protection against retinal I/R injury.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Whether these metabolites in the KP affect RGCs was less studied. During our study, a study by Harper et al [25] showed that systemic inhibition of KMO protects RGCs in an experimental mouse model for traumatic brain injury, supporting the idea that KP metabolites play a role in RGC health. We found that the absence of KMO led to higher levels of KYN, KYNA and AA in the serum and retina, coincident with a protection against retinal I/R injury.…”
Section: Discussionsupporting
confidence: 83%
“…High levels of QUIN and 3OHKYN and reduced levels of KYNA have been observed in the brains of Huntington's disease patients [21][22][23]. It has been found that traumatic brain injury activates the KP resulting in elevated QUIN [24], and another study showed that KMO plays an important role in RGC death in mice subjected to traumatic brain injury [25]. Previous studies have shown that the absence of KMO activity resulted in beneficial effects by reducing inflammation and a reduction in peripheral lipopolysaccharide-induced depressive-like behaviors in mice [26].…”
Section: Introductionmentioning
confidence: 99%
“…We followed a well-established protocol to identify RGCs via BRN3A immunohistochemistry, as previously described. 32 After euthanasia, mice were transcardially perfused with 0.01-M PBS followed by 4% paraformaldehyde in 0.01-M PBS. Ipsilateral whole eyes were enucleated and posterior cups were dissected and fixed for 4 hours at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the method of inducing blastmediated TBI that was used in this study results in uniform damage among mice exposed to blast. Previously published transcriptomic studies using this model demonstrates very little intra-animal variability in gene expression changes [87].…”
Section: Discussionmentioning
confidence: 85%